How The Leopard Got His Spots - Kimberley Scott (Illustrator); Miles Kelly Publishing
In the yellow hues of the African plains, hunting was easy for the leopard, whose light coat served as camouflage. When all the animals moved away, the hungry leopard had to follow them to the striped, splotchy, spotted forest. But he didn't stand a chance of survival unless, of course, he acquired spots himself. Rich in language and subtle humor, this inspired adaptation of the Rudyard Kipling classic comes alive.